IMPROVING STUDENTS’ ACHIEVEMENT ON WRITING NARRATIVE TEXT BY USING CLUSTERING TECHNIQUE - Ika Purnama and Johan Sinulingga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study focused on the improvement of students’ achievement on writingnarrative text by using Clustering technique. The main objective of this study toknow whether clustering technique could significantly improve students’achievement in writing narrative text. It was conducted by applying classroomaction research which consisted two cycles in six meetings. Every meetingconsisted of four phases. The subject of this study was second grade students ofSMA Perguruan Sumatera Tanjung Morawa. Total of students was 29. Theinstruments for collecting data were writing tests for quantitative data and diarynotes, observation sheet, questionnaire sheet for qualitative data. Based on thestudents’ test, the students’ score was improved in every test. In Test I, the meanscore was 59,41. In the Test II, the mean score was 69,65. In the test III, the meanscore of the students was 78,17. The using clustering technique in every test tendsto be more effective. So, the mean of test improves and gets better.